MANIFESTATION OF IRIS YOUNGS OPPRESSION IN THE NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM BY DIAN PURNOMO - Saragih, Wima Alfa Zaliani; Sariasih, Yanti; Ekawati, Mursiah (Universitas Muhammadiyah Makassar, 2026)
Research on oppression against women in novels is motivated by the complex representation of injustice and oppression against women in literary works as a reflection of patriarchal society. The purpose of this study is to analyze the manifestations of oppression in Dian Purnomo's novel Perempuan yang Menangis kepada Bulan Hitam using Iris Young's theory of oppression. This is a qualitative study with descriptive methods. This study takes a literary feminist approach, drawing on Iris Young's five faces of oppression theory, which includes cultural imperialism, marginalization, powerlessness, exploitation, and violence. The main data for this study comes from Dian Purnomo's novel, Perempuan Yang Menangis Kepada Bulan Hitam. This study uses data that includes excerpts of sentences, monologues, dialogues, and paragraphs that contain practices of oppression against female characters. Data collection in this study was carried out using observation and recording, while data analysis was carried out using content analysis. The findings in this study confirm that Dian Purnomo's novel Perempuan Yang Menangis Kepada Bulan Hitam manifests the reality of women's lives trapped under an oppressive patriarchal structure and reveals criticism of gender inequality in society. These forms of oppression are interrelated and manifested through cultural imperialism in the form of Yappa Maniwe culture, which then leads to the marginalization of women in social environments, the powerlessness of women in decision-making, sexual exploitation, and physical and mental violence.